Implicature Analysis of Milk Advertising - Muhammad Mustofa Aqil (Politeknik Siber Cerdika Internasional, 2024)
This study aims to describe the types of implicatures contained in milk advertisements. This type of research is descriptive qualitative. The data collection method used in this study is the listening method with basic techniques as the basic technique. The free engagement listening technique can be used as an advanced technique. The data that has been collected will be analyzed using the Pragmatic equivalent method using the determinant element sorting technique which has a research tool in the form of sorting power which is useful for differentiating reactions and hearing levels. From the results of the analysis the authors found more types of unconventional implicature, because the statements conveyed are not general in nature. The type of advertisement that is displayed has a conversation that only one speaker understands and that is a creative form of the advertisement that is presented. The advertisement does not seem boring and makes the audience curious. The type of advertisement that is displayed has a conversation that only one speaker understands and that is a creative form of the advertisement that is presented. The advertisement does not seem boring and makes the audience curious. The type of advertisement that is displayed has a conversation that only one speaker understands and that is a creative form of the advertisement that is presented. The advertisement does not seem boring and makes the audience curious.